PEMULIHAN PSIKOLOGI-SOSIAL PASCA GEMPA OLEH GURU DI KABUPATEN BANTUL DIY - Irene_Astuti D, Siti (LPMPP Universitas Negeri Yogyakarta, 2008)
Recovery is necessary-for society- to rearrange their life after the earthquake.Teachers as society -memberstry to provide social supports as an attempt toovercome problems resulting from the earthquake. Social supports asan importantpart of the recovery process have positive effects on society members. This studyrevealed how teachers helped the recovery process after-the earthquake in BantulRegency, Yogyakarta Special Territory. Thestudy employed the qualitativeapproach. Thedata were collected through in depth interviews, observations, anddocuments. The data were analyzed by using the descriptive and narrativetechniques. In the post-earthquake situation, teachers established resilience torecover their own life spirit and their students'. It was not easy for them to do sobecause mostof them experienced a traumatic situation during the earthquake.They tried toapply resilience strategies in the recovery process. For them,difficulties that the students faced were not only damagedand destroyed schoolbUildings which were not conducive for learning. For them, the earthquake was alearning experience tounderstand more about life. They realized their limitation asGod's creatures, social creatures,and individual creatures. In the recovery process,teachers, especially thosein Pleret District, expressed their creatiVity in a rationaland positive attitude towards the earthquake by joining a variety of spiritual-andsocial activities. They accompanied the students in difficult situations. They statedthat they could not realize the helping process to the maximum due to their owninternal problems. They stated that the earthquake -managed to improve theirunderstandingof the meaning of life and was the beginning of a process oflearning the earthquake as natural event that might happen any time in Indonesia